1989
DOI: 10.1111/j.1365-2141.1989.tb07677.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface marker expression in adult acute myeloid leukaemia: correlations with initial characteristics, morphology and response to therapy

Abstract: The clinical significance of surface markers was investigated in 145 cases of acute myeloid (AML) or undifferentiated leukaemia (AUL), using a panel of six monoclonal antibodies directed to NHL-30.5 antigen (expressed on poorly differentiated myeloid cells), CD13, CD14, CD15, CD33 and CD34 antigens. Expression of CD14 was correlated with higher leucocyte count, higher serum lactate dehydrogenase level and presentation with extramedullary disease. There was no strict correlation with the French-American-British… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
2
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(48 citation statements)
references
References 28 publications
4
40
2
2
Order By: Relevance
“…This report highlights specifically the fact that the prognostic value of an individual antigen's expression depends on the immunological differentiation stage of the leukemic cells. The present study demonstrated that antigens whose expression had already been shown as a potential prognostic factor (CD34,-CD7,-CD14) (19)(20)(21)(22)(23)(24)(25)(26)(27)(28) were indeed related to outcome in the overall population. More interestingly, their prognostic value, which could be marginal in the overall population, became strongly significant in specific immunological AML subsets while it retained no significance in other subsets.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This report highlights specifically the fact that the prognostic value of an individual antigen's expression depends on the immunological differentiation stage of the leukemic cells. The present study demonstrated that antigens whose expression had already been shown as a potential prognostic factor (CD34,-CD7,-CD14) (19)(20)(21)(22)(23)(24)(25)(26)(27)(28) were indeed related to outcome in the overall population. More interestingly, their prognostic value, which could be marginal in the overall population, became strongly significant in specific immunological AML subsets while it retained no significance in other subsets.…”
Section: Discussionmentioning
confidence: 79%
“…The frequency of CD34 expression was similar in these two subsets as compared to other immunological AML subsets, and was not related to specific FAB subgroups, which indicates that MA and MD indeed define specific entities. Conversely, CD14, more frequently expressed in AML with a monocytic component, (21)(22)(23)30) appeared related to a poor outcome only in MD and ME subsets. The prognostic value of CD14 expression was independent of the FAB classification in the MD subset and had already been reported in such FAB subsets as M3 (22) or M0.…”
Section: Discussionmentioning
confidence: 99%
“…Higher age, high white blood cell count at diagnosis, and M 0 morphology have been recognized as clinically adverse prognostic factors in AML. Additional biological or disease-related prognostic variables which are associated with a poor survival include higher age, hyperleucocytosis, autonomous leukaemia growth in vitro, expression of the immature stem cell antigen CD34 and karyotypic abnormalities such as monosomy 7, 5q¹, 7q¹, the Philadelphia chromosome (t(9;22) and a complex karyotype (Campos et al, 1989;Löwenberg et al, 1993;Machnicki & Bloomfield, 1990). On the other hand, cytogenetic abnormalities such as inv(16), t(8;21) and t(15;17) are associated with a good response to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the CD34 glycoprotein, which is expressed on immature myeloid cells, has been generally correlated with lower remission induction rate and shorter overall survival. [3][4][5][6][7][8][9][10] Among different mechanisms considered responsible for the chemoresistance of immature myeloid leukemic cells to DNR, the multidrug resistance phenotype (MDR) appears to play an important role. Indeed, in bulk leukemic cells taken from the blood or the marrow of patients with de novo or secondary AML, as well as in AML cell lines, CD34 expression has been correlated with both the mdr1 gene and P-glycoprotein (Pgp) overexpression.…”
Section: Introductionmentioning
confidence: 99%